2017
DOI: 10.29252/arakmu.11.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Silymarin and D-Penicillamine on Lead Induced Hemotoxicity and Oxidative Stress in Rat

Abstract: Background: This study was performed to investigate the adverse effects of acute lead

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Exposure of rats to lead Yusuf et al 11 induced a significant increase in erythrocyte osmotic fragility (EOF) in the experimental animals. This result is in line with previous studies as carried out by Jalali et al (2017), who found similar results as that reported in this study. The increase could be ascribed to the increase in the generation of reactive oxygen species (ROS) following oxidative damage, as caused by lead.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Exposure of rats to lead Yusuf et al 11 induced a significant increase in erythrocyte osmotic fragility (EOF) in the experimental animals. This result is in line with previous studies as carried out by Jalali et al (2017), who found similar results as that reported in this study. The increase could be ascribed to the increase in the generation of reactive oxygen species (ROS) following oxidative damage, as caused by lead.…”
Section: Discussionsupporting
confidence: 83%
“…Tissue damage has also been reported in the pathophysiology of lead poisoning, with increasing evidence that oxidative stress plays an important role in the pathology of lead poisoning (Jalali et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among the parts of the human body and systems hematopoietic, renal, reproductive, and central nervous systems are more vulnerable toward the dangers from exposure to high levels of lead. 4 According to Jalali et al (2017), the elevation of malondialdehyde (MDA) level increases erythrocyte superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities along with a rise in total leukocyte, lymphocyte, and neutrophil counts, resulting into microcytic anemia in the lead treated rats. 5 Chelation therapy is the conventional suggestion for low-level lead poisoning with brain (encephalopathic) damage.…”
Section: Introductionmentioning
confidence: 99%
“…4 According to Jalali et al (2017), the elevation of malondialdehyde (MDA) level increases erythrocyte superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities along with a rise in total leukocyte, lymphocyte, and neutrophil counts, resulting into microcytic anemia in the lead treated rats. 5 Chelation therapy is the conventional suggestion for low-level lead poisoning with brain (encephalopathic) damage. However, the treatment with low amounts but for longer duration is still under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…[12]. It is a free radical scavenger and a membrane stabilizer that prevents lipoperoxidation and reduced glutathione depletion in some experimental models [13]. It has been also reported that having multiple pharmacological activities including hepatoprotectant, an anti-inflammatory agent, antibacterial, anti-allergic, antiviral, anti mutagenic, antineoplastic, and antithrombotic agent [14].…”
Section: Introductionmentioning
confidence: 99%